2022
DOI: 10.1007/s10853-022-07121-y
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive quantitative characterisation of the multiphase microstructure of a thick-section high strength steel

Abstract: The through-thickness heterogeneous microstructure of thick-section high strength steels is responsible for the significant scatter of properties along the thickness. In this study, in order to identify the critical microstructural features in the fracture behaviour and allow for design optimisation and prediction of structural failure, the through-thickness microstructure of thick-section steels was extensively characterised and quantified. For this purpose, samples were extracted from the top quarter and mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Several studies [82,[95][96][97][98][99][100] have quantified the distribution of second-phase particle number densities for several high-strength steels (Table 2), for second-phase particle number densities in the range of 10 2 -10 3 particles/mm 2 . The nominal upper and lower bounds for η were selected as 250 and 4000 particles/mm 2 , respectively, for the parameter sensitivity study.…”
Section: Part Ii: Parameter Sensitivity Study 221 Second Phase Partic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [82,[95][96][97][98][99][100] have quantified the distribution of second-phase particle number densities for several high-strength steels (Table 2), for second-phase particle number densities in the range of 10 2 -10 3 particles/mm 2 . The nominal upper and lower bounds for η were selected as 250 and 4000 particles/mm 2 , respectively, for the parameter sensitivity study.…”
Section: Part Ii: Parameter Sensitivity Study 221 Second Phase Partic...mentioning
confidence: 99%
“…The grain size sensitivity exponent, Z, has been calibrated for a variety of materials, including steel [112]. Grain sizes in steel have been shown to vary from 1 µm in diameter for high-strength steels (and even less than 1 µm in specially designed ultra-fine-grain materials) to greater than a 100 µm size for mild steels [98,105,113]. The bounds for the grain size term, GS, were selected as 1 µm and 100 µm, accordingly.…”
Section: Grain Sizementioning
confidence: 99%
“…Xie et al studied the influence of holding time on carbide size and distribution in 960 Mpa grade low alloy steel, and found that prolonging the holding time leads to the coarsening of carbides [19]. in terms of research on the models and characterization of material grain size distribution [20][21][22][23], Yu et al studied the non-uniformity of microstructure in both 2 and 3 mm-thick Dp600 thin plates, and established models for accurately describing the non-uniform distribution of microstructure in thin plate [20]. Kazakov et al investigated the microstructural non-uniformity of 25-70 mm hot-rolled thick plates and proposed a method to evaluate microstructural anisotropy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Kazakov et al investigated the microstructural non-uniformity of 25-70 mm hot-rolled thick plates and proposed a method to evaluate microstructural anisotropy [21]. Yamashita et al analyzed the influence of friction stir welding on the non-uniformity of microstructure along the thickness direction in 2 mm dual-phase stainless steel, and revealed the variation of grain size in the α and γ phases along the thickness direction [22]. virgínia et al found the non-uniformity of microstructure in quarter and middle thicknesses of 80 mm-thick S690Ql high-strength steel and proposed a characterization method for the multiphase microstructure of quenched and tempered high-strength steel [23].…”
Section: Introductionmentioning
confidence: 99%